2014
DOI: 10.2478/ahbb-2014-0003
|View full text |Cite
|
Sign up to set email alerts
|

Neophytes In Protected Areas. Case Study: The Danube Delta Biosphere Reserve

Abstract: Abstract:The Danube Delta is a relatively young territory, formed about 14,000 years ago. It has quadruple status: Biosphere Reserve, Ramsar site, UNESCO World Heritage site, Natura 2000 site. Water and human activities are the most important factors influencing the flora of this area, including the penetration and spread of alien plants. The main goal of our research in this area was to inventory the alien plants and to identify those species which are invasive and potentially invasive in the natural and semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…As a response, there are many publications devoted to alien plant performances in Protected Areas (e.g. Allen et al, 2009;Sennikov, 2012;Khapugin et al, 2013;Shcherbakov et al, 2013;Anastasiu et al, 2014;Burda et al, 2015;Fateryga & Bagrikova, 2017) and their number is increasing rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…As a response, there are many publications devoted to alien plant performances in Protected Areas (e.g. Allen et al, 2009;Sennikov, 2012;Khapugin et al, 2013;Shcherbakov et al, 2013;Anastasiu et al, 2014;Burda et al, 2015;Fateryga & Bagrikova, 2017) and their number is increasing rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…Amorpha fruticosa and Robinia pseudoacacia have been scored as being of very high impact on the habitats in the "Iron Gates" Natural Park [20]. In habitats from Danube Delta Biosphere Reserve, Anastasiu et al [6] reported as invasive some nNOP (Ailanthus altissima, Echinocystis lobata, Elaeagnus angustifolia, Fraxinus pennsylvanica, Lycium barbarum, Morus alba and Phytolacca americana), but pointed out that some species recorded as escaped from cultivation are known as invasive in other regions or countries: Asclepias syriaca, Helianthus tuberosus, Parthenocissus inserta, Rudbeckia laciniata and Solidago gigantea.…”
Section: Discussionmentioning
confidence: 99%
“…The analyses performed for this paper considered a total of 362 non-native plant species introduced and used for their horticultural or other ornamental value (nNOP) [5,6,8,20,32,33,34,35,46,47,48,49]. Taxa not reported in the last 50 years were evaluated as vanished and they were excluded from the updated list.…”
Section: Methodsmentioning
confidence: 99%
“…A South American plant that is cultivated as an ornamental ( Király 2009 ). It appears as an ephemeral casual alien in some European countries, for example, Romania ( Anastasiu et al 2009 ). Balogh et al (2004) and Csiky et al (2023) list it as a casual alien.…”
Section: Taxon Treatmentsmentioning
confidence: 99%